Validação da escala Homo Zappiens-tecnologias digitais para avaliação do uso das TICs na aprendizagem dos alunos do terceiro ano do ensino médio no Colégio Militar em Fortaleza/CE: estudo de caso - Lopes, Julio Cesar Vieira (2018)
This academic project expresses the configuration of the profile of the students of the 3rd year of high school of the Military College of Fortaleza (CMF). The theoretical basis is based on the theories formulated by Jean Piaget and Reuven Feuerstein. The problematic underlying the empirical reality is concretized in the scientific context through the paradigm of descriptive research in the field in the qualitative approach. The subjects of the research constitute a group of 120 students enrolled in the third year of high school. The students' learning performance is analyzed by means of the categories: students who are both insolvent and non-bankrupt, migrants and non-migrants. The general objective of the study was to validate the Homo-Zappiens Tecnologias Digitais scale for the evaluation of the academic performance of the students of the third year of high school in the Military School in Fortaleza / CE, with a view to characterizing the profile of students regarding the use of ICT in their learning procedures. The specific objectives delineated: to explain the quality of the measurement instrument Homo Zappiens-Digital Technologies scale by means of the validation of the theoretical constructs; to delineate students' performance in the Assessment of Study (AE) in Mathematics in the year 2017 and the grade of Mathematics in the first quarter of 2018; to describe students' perceptions of ICTs by identifying the construct homo zappiens; to compare the indicators of non-verbal intelligence (G-36) with the indicators of the performance measured in the Homo Zappiens-Tecnologias Digitais scale and the academic performance of the students, as well as to analyze the results of the academic performance of the students admitted by competitions and non- through the influence of the homo zappiens constructs. The methodological procedures for the collection of the primary data are effected through informal conversations, interviews, testimonies, and application of the measurement instruments. The secondary data were captured in the database of the Adventist Control Secretariat of the Institution. Data processing and analysis were performed by the software Statistical Package for the Social Sciences (SPSS), processed by Windows, version 22.0 It was concluded that there is a significant difference between CMF students admitted as insolvent and non-insolvent. It is recommended that the study be replicated for the validation of the research findings.